IMPLEMENTASI MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPA DI SMP Al-MUHAJIRIN DEPOK - Siskandar siskandar; Farizal MS; Rangga Umbara K (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2022)
This study aims to determine how the problem-based learning model in science learning at Al-Muhajirin Depok Junior High School is applied. This research is a qualitative research with a case study approach. This study explores field data that is confirmed by other supporting sources. The results of the study focused on three things, namely to find out to what extent the teacher's understanding in implementing the Problem Based Learning (PBL) Model in Science Learning at SMP Al - Muhajirin Depok, To find out how the strategy for implementing the Problem Based Learning (PBL) Model in improving science learning in junior high schools Al - Muhajirin Depok, to find out the extent of the benefits of PBL in science learning in improving student learning outcomes. The implementation of the problem-based learning model at SMP Al-Muhajirin Depok is divided into two parts of the task, namely: assignments in class, by analyzing and solving problems from the material provided through the media of images or videos, and assignments outside the classroom, namely by conducting analysis and observation for identify biotic and abiotic components in aquatic and terrestrial environments, and make products or manage non-organic materials into interesting and unique items. This problem based learning model aims to improve science learning at SMP AL-Muhajirin Depok, because science learning requires more scientific results in learning. This model is quite effective because the application of this model can help improve science learning. This is evidenced by the results of the average grade VII grade report cards in science learning at SMP Al-Muhajirin Depok in the 2019/2020 academic year